Open service platform for IoT - Hao RONG; GLingyun JIAN (Dianxin kexue)
Currently，there are still some problems with IoT，specifically in：one is that the IoT gives priority to vertical service system；another is the lack of cross-system resource sharing.To solve the above problems，a scalable intelligence service architecture of IoT in which a unified service data model was proposed and a message middleware were built to overcome the multi-source heterogeneous problems in the data structure，data platforms and operating systems. In addition，a usage authorization mechanism was proposed to support security and privacy in the IoT environment， contributing to a scalable，secure and reliable intelligence open service platform for IoT.Finally，a prototype system was designed and concrete system was given to verify the feasibility and superiority of the proposed architecture.